Assessment of the Potential of Vaccination to Combat Antibiotic Resistance in Gonorrhea: A Modeling Analysis to Determine Preferred Product Characteristics. (6th January 2020) - Whittles, Lilith K; White, Peter J; Didelot, Xavier
Abstract: Background: Gonorrhea incidence is increasing rapidly in many countries, while antibiotic resistance is making treatment more difficult. Combined with evidence that two meningococcal vaccines are likely partially protective against gonorrhea, this has renewed interest in a gonococcal vaccine, and several candidates are in development. Key questions are how protective and long-lasting a vaccine needs to be, and how to target it. We assessed vaccination's potential impact and the feasibility of achieving the World Health Organization's (WHO) target of reducing gonorrhea incidence by 90% during 2018–2030, by comparing realistic vaccination strategies under a range of scenarios of vaccine efficacy and duration of protection, and emergence of extensively-resistant gonorrhea. Methods: We developed a stochastic transmission-dynamic model, incorporating asymptomatic and symptomatic infection and heterogeneous sexual behavior in men who have sex with men (MSM). We used data from England, which has a comprehensive, consistent nationwide surveillance system. Using particle Markov chain Monte Carlo methods, we fitted to gonorrhea incidence in 2008–2017, then used Bayesian forecasting to examine an extensive range of scenarios. Results: Even in the worst-case scenario of untreatable infection emerging, the WHO target is achievable if all MSM attending sexual health clinics receive a vaccine offering ≥ 52% protection for ≥ 6 years. A vaccine conferring 31% protection (as estimated for MeNZB) for 2–4 years could reduce incidence in 2030 by 45% in the worst-case scenario, and by 75% if > 70% of resistant gonorrhea remains treatable. Conclusions: Even a partially-protective vaccine, delivered through a realistic targeting strategy, could substantially reduce gonorrhea incidence, despite antibiotic resistance. Abstract : A gonorrhea vaccine offering partial protection for several years, pragmatically targeted to people testing for gonorrhea due to symptoms or screening due to sexual risk behavior, could substantially reduce gonorrhea incidence, combating increases in antibiotic resistance.